1998
DOI: 10.1097/00006842-199809000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Stress and Illness in Children

Abstract: Results provide the first evidence that CVR may mediate the relation between household density and medical illness in children. More generally, these findings support the role of allostasis as an underlying mechanism in the link between chronic stress and health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(44 citation statements)
references
References 41 publications
1
41
0
2
Order By: Relevance
“…They found that the amount of morphine received was indeed the best predictor of the future development of PTSD. Other studies have supported the relationship between chronic psychologic and environmental stress and health and well-being in children in non-medical populations [14]. Such studies emphasize that children may be particularly vulnerable to the impact of stress on chronic health conditions.…”
Section: Review Of the Literaturementioning
confidence: 93%
“…They found that the amount of morphine received was indeed the best predictor of the future development of PTSD. Other studies have supported the relationship between chronic psychologic and environmental stress and health and well-being in children in non-medical populations [14]. Such studies emphasize that children may be particularly vulnerable to the impact of stress on chronic health conditions.…”
Section: Review Of the Literaturementioning
confidence: 93%
“…When the body is under stress, allostasis, the body's ability to adapt to environmental demands [21], is threatened. When allostasis is threatened, undesirable changes may occur in the immune system [22].…”
Section: Stressmentioning
confidence: 99%
“…An important new line of research involves the use of concomitant biological measures of allostatic load, such as glycosylated proteins, coagulation/fibrinolysis markers and immune markers [47]. Johnston-Brooks et al [48], for instance, associated household density as a chronic environmental stressor with cardiovascular reactivity as a marker of allostatic load and found a relationship with medical illness in children. The need of combining psychometric and biological measures in laboratory research involved with psychoneuroendocrinology of human disease has therefore emerged [49, 50].…”
Section: Psychosocial Factors Affecting Individual Vulnerabilitymentioning
confidence: 99%